Product design specification (PDS) development for developing an assistive walking device for elderly - Yap, Mei Shy; Dolah, Mohd Shahrizal; Shahbudin, Shahrul Azman; Abdul Rahman, Ahmad Rizal; Hussain, Mohd Rizal; Ramly, Saiful Hasley (Universiti Putra Malaysia Press, 2020)
Ageing is an issue occur globally. Malaysia is one of the countries which is slowly stepping into the ageing nation. As the number of elderlies increased, the fall risk prevalence has become as one of the major issues among the elderly. An Elderly tend to experience higher fall risk and more severe injury cause compare to other age group since some of the fall factors are age-related. Therefore, the purpose of this study is to analyze the public perception, behavior on the use of walking aids and to develop product design specification (PDS) for developing an assistive walking device with better user experience and efficiency to reduce fall risk among elderly. Mix-methods were used to carry out this study consist of observation and questionnaire. 100 respondents were involved in this study that was focusing care center in Klang Valley Malaysia. Majority of the respondents agreed that the existing walker causes unpleasant user experience due to improper walker sizing and ergonomic issues. PDS will be proposed in developing an assistive walking device to enhance the effectiveness of the device in reducing elderly fall risk. The outcome of the PDS will contribute to walker users, people with disabilities, senior citizen, elderly caretaker and guidance for product designer.